The Influence of Working Assets Efficiency Management on the Profitability of Trade in Serbia - Radojko LUKIC (Revista de Management Comparat International)
The efficiency of working assets (working capital) management is one of the crucial factors of performance in trade. It is quite understandable when one takes into account the fact that the biggest part of total assets of the trading companies is related to working assets, i.e. inventories as a part of current assets. With the application of appropriate methodology this paper explores determinants and impact of efficiency of working assets management on the profitability of trade in Serbia for the 2008-2012 period, based on an example of commercial companies which are required by law to submit the final financial statements. General conclusion is that there was insufficient efficiency of working assets in observed period, which was reflected on the profitability of trade in Serbia. Related to this, it is necessary to take all relevant measures to improve the efficiency of working assets in order to increase the profitability of trade in Serbia. This especially applies to the application of modern information and communication technologies, particularly in the supply chain management (enterprise resource planning system, RFID).